2014
DOI: 10.1166/jnn.2014.8658
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gold Microstructures with Surface Nanoroughness Using a Deep Eutectic Solvent for Catalytic and Diagnostic Applications

Abstract: We synthesized highly monodisperse gold microparticles (AuMPs) using a deep eutectic solvent (DES) which composed of choline chloride and malonic acid as both a reaction medium and structure-directing agent. These microparticles exhibit distinctive surface nanoroughness and highly defined diameters that can be precisely controlled over a range of a few micrometers under different reductive conditions. The internal and external structures of the particles are thoroughly investigated by electron microscopy, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…ILs and DESs have been widely used as efficient dispersants during the synthesis reaction of nanoproducts. They have played roles in determining the shape, size and morphologies [47][48][49]. They are also capable of splitting small-scale structures into nano-scale and this aspect is added to their use as a functional dispersing solvent.…”
Section: Media To Disperse Nanoparticles and Control Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…ILs and DESs have been widely used as efficient dispersants during the synthesis reaction of nanoproducts. They have played roles in determining the shape, size and morphologies [47][48][49]. They are also capable of splitting small-scale structures into nano-scale and this aspect is added to their use as a functional dispersing solvent.…”
Section: Media To Disperse Nanoparticles and Control Morphologymentioning
confidence: 99%
“…Oh et al [49] used a DES of ChCl and malonic acid as both a reaction medium and structure-directing agent to synthesize highly monodisperse gold microparticles. The product had a distinctive surface nanoroughness and highly defined diameters controlled precisely under different reductive conditions.…”
Section: Media To Obtain Special Sizes and Morphologies Of Nanomaterialsmentioning
confidence: 99%
“…The DES used served as solvent and catalyst for the condensation of furfuryl alcohol, followed by carbonization resulting in the formation of pores. Oh et al reported synthesizing highly monodispersed gold particles with a distinct rough surface and defined diameters using choline chloride and malonic acid [89].…”
Section: Deep Eutectic Solvents In Nanotechnologymentioning
confidence: 99%
“…46,48,49 To the best of our knowledge, only few studies have focused on the effect of water content on the electrochemical behaviour of DES 44,50,51 , as well as on the electrodeposition of nanomaterials. 52 On the one hand, water content has been proven essential to control the electrochemical properties of the DES. In fact, the presence of small amounts of water (up to 6 wt %), has shown to be beneficial for obtaining more uniform and compact Ni coatings.…”
Section: Introductionmentioning
confidence: 99%